2002
DOI: 10.1002/da.10045
|View full text |Cite
|
Sign up to set email alerts
|

Achieving remission with venlafaxine and fluoxetine in major depression: its relationship to anxiety symptoms

Abstract: Venlafaxine, a serotonin and norepinephrine reuptake inhibitor (SNRI), produces significantly higher remission rates in depressed patients than do the selective serotonin reuptake inhibitors (SSRIs). In this analysis of pooled data, we explored the relationship between differences in treatment efficacy, early improvement of symptoms, and severity of baseline anxiety in depressed patients treated with either venlafaxine or fluoxetine. A pooled analysis was performed on data from 1,454 outpatients with major dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 32 publications
3
66
1
4
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12] In MDD patients without mixed features, the presence of concurrent anxiety has been shown to reduce the likelihood of achieving an adequate antidepressant response. [19][20][21][22][23][24][25][26][27] We report here the results of a post-hoc analysis of a placebo-controlled, 6-week trial of MDD presenting with mixed features and anxiety which found that treatment with lurasidone significantly improved depressive symptoms in a subgroup of patients with moderate-to-severe anxiety at baseline. Significant improvement was also noted in the subgroup with mild anxiety at baseline.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12] In MDD patients without mixed features, the presence of concurrent anxiety has been shown to reduce the likelihood of achieving an adequate antidepressant response. [19][20][21][22][23][24][25][26][27] We report here the results of a post-hoc analysis of a placebo-controlled, 6-week trial of MDD presenting with mixed features and anxiety which found that treatment with lurasidone significantly improved depressive symptoms in a subgroup of patients with moderate-to-severe anxiety at baseline. Significant improvement was also noted in the subgroup with mild anxiety at baseline.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] Notably, treatment with lurasidone has previously demonstrated significant anxiolytic treatment effects in three separate 6-week trials in bipolar depression. [33][34][35] While further studies are necessary to confirm these findings, the results of the current analysis, taken together with the consistent improvements in HAM-A scores observed in prior bipolar depression studies, suggest that lurasidone may be a useful treatment for mixed forms of major depression associated with anxiety.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
See 1 more Smart Citation
“…Its findings indicated that venlafaxine was superior to SSRIs (Smith et al, 2002). Another meta-analysis of five sixweek, double-blind, randomized studies including 1,454 outpatients with major depression from comparing the efficacy of venlafaxine with fluoxetine showed that venlafaxine was not www.intechopen.com only superior to but also had a more rapid onset of action than fluoxetine (Davidson et al, 2002). The rapid onset of remission for venlafaxine treatment over SSRIs does not differ in age or gender .…”
Section: Serotonin Norepinephrine Reuptake Inhibitors Vs Selective Smentioning
confidence: 99%
“…Многолетний успешный мировой опыт приме-нения венлафаксина свидетельствует об дозозави-симом механизме его действия, что дает возмож-ность использовать препарат в качестве альтерна-тивы СИОЗС и трициклическим антидепрессантам при лечении и терапевтически резистентных де-прессий, и остро развившейся первичной депрес-сии как в стационарной, так и амбулаторной прак-тике [7,[14][15][16][17][18][19]. Подчеркиваются благоприятный профиль переносимости и невысокая частота по-бочных эффектов в ходе терапии венлафаксином [14].…”
unclassified